2022
DOI: 10.1002/advs.202203856
|View full text |Cite
|
Sign up to set email alerts
|

Smart Electronic Textile‐Based Wearable Supercapacitors

Abstract: Electronic textiles (e-textiles) have drawn significant attention from the scientific and engineering community as lightweight and comfortable next-generation wearable devices due to their ability to interface with the human body, and continuously monitor, collect, and communicate various physiological parameters. However, one of the major challenges for the commercialization and further growth of e-textiles is the lack of compatible power supply units. Thin and flexible supercapacitors (SCs), among various en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 540 publications
0
79
0
Order By: Relevance
“…The initial capacitance values ( C 0 ) of the TPU fiber-based sensor, the TPU@IL 1.7 ionogel fiber-based sensor, and the TPU@IL 2.6 ionogel fiber-based sensor are 0.5 pF, 6 pF, and 12 pF, respectively. The UAC values of these sensors are 464, 456,000, and 656,000 nF·cm –2 , respectively (Figure S4), which are obtained based on galvanostatic charge/discharge curves according to the literature. Clearly, compared with the TPU fiber-based sensor without IL, TPU@IL ionogel fiber-based sensors show significantly improved C 0 and UAC, which helps increase the noise immunity, detection resolution, and device sensitivity. From Figure a, it is found that the TPU fiber-based sensor exhibits a low noise immunity and poor cyclic stability due to the relatively low C 0 and UAC.…”
Section: Resultsmentioning
confidence: 84%
“…The initial capacitance values ( C 0 ) of the TPU fiber-based sensor, the TPU@IL 1.7 ionogel fiber-based sensor, and the TPU@IL 2.6 ionogel fiber-based sensor are 0.5 pF, 6 pF, and 12 pF, respectively. The UAC values of these sensors are 464, 456,000, and 656,000 nF·cm –2 , respectively (Figure S4), which are obtained based on galvanostatic charge/discharge curves according to the literature. Clearly, compared with the TPU fiber-based sensor without IL, TPU@IL ionogel fiber-based sensors show significantly improved C 0 and UAC, which helps increase the noise immunity, detection resolution, and device sensitivity. From Figure a, it is found that the TPU fiber-based sensor exhibits a low noise immunity and poor cyclic stability due to the relatively low C 0 and UAC.…”
Section: Resultsmentioning
confidence: 84%
“…In addition, transition metals with various oxidation numbers are advantageous for supercapacitors that charge and discharge via redox reactions. 64,65 For example, they undergo Ni 2+ /Ni 3+ , Cu 2+ /Cu 3+ , and Zn 2+ /Zn 3+ oxidation-reduction reactions. At the same time, the faradaic redox reaction widely appears with Ni-O-OH, Cu-O-OH, and Zn-O-OH in the Ni, Cu, and Zn parts, respectively.…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…Conductive polymers such as PANI, PPy, PT, and biodegradable polymers such as poly­( d , l -lactic acid) (PDLLA) and PCL can be covalently bound together, enabling the ability to “tailor and engineer” the performance and sustainability properties of the final polymeric material. However, an ongoing challenge for organic-based conductive polymers is that the material’s longevity is relatively poor, specifically the inadequate cycling performance of conductive polymers in applications such as supercapacitor electrodes , in wearable electronics. To overcome this technical deficiency, incorporating carbon-based materials into conductive polymers is a promising approach to enhancing their overall electrochemical performance by integrating the optimal individual properties of both components leading to better utilization and sustainability.…”
Section: Sustainable Materialsmentioning
confidence: 99%